2022
DOI: 10.1007/s00168-022-01203-0
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial ecosystems in conflict regions: evidence from Ukraine

Abstract: Entrepreneurship is a productive force of innovation and economic development. However, in post-conflict regions, there is a greater challenge in allocating entrepreneurial talent to productive entrepreneurship. In this study, we examine the entrepreneurship ecosystem, which is built on the “bottom-up” principles to understand whether its pillars can facilitate productive entrepreneurship in two Ukrainian regions shaken by multiple revolutions and regime change. We introduce a model that puts entrepreneurial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…In my city (region), There is a growth-oriented (strong and productive) entrepreneurship ecosystem [20], [21]. In my region (city), There is a adequate formal network to back up entrepreneurship ecosystem [22].…”
Section: Strong and Growthoriented Entrepreneurshipmentioning
confidence: 99%
See 1 more Smart Citation
“…In my city (region), There is a growth-oriented (strong and productive) entrepreneurship ecosystem [20], [21]. In my region (city), There is a adequate formal network to back up entrepreneurship ecosystem [22].…”
Section: Strong and Growthoriented Entrepreneurshipmentioning
confidence: 99%
“…Research on the role of ecosystem entrepreneurship has been identified with two approaches. First, it was measured toward each element's contributions [19], [20], [22], [25]. Second, some authors calculated it with an indexing approach that divided in into three measurements such as additive [18], [21], [24], multiplicative [11], and logarithmic [12].…”
Section: Entrepreneurial Ecosystem Index To Productive Entrepreneurshipmentioning
confidence: 99%